In vitro toxicity evaluations of Tibetan medicine Zuota from four institutions. (2nd April 2016) - Li, Bo; Li, Yan-Dan; Yang, Zhengming; Chen, Yijun; Liu, Panpan; Liu, Yuan; Zhang, Zhi-Feng; Lv, Lu-Yang; Zhang, Ji-Zhong; Zeng, Rui; Li, Li-Min
Abstract: Zuota is regarded as the king of Tibetan medicine. However, the major starting material of Zuota is mercury, which is one very toxic heavy metal. This has aroused serious doubts on the biosafety of Zuota containing drugs. In this study, we quantified the Hg contents in four Zuota samples, monitored the release of Hg in simulated gastric/intestinal juice and evaluated their cytotoxicity to Caco-2 cells. Our results showed that the Hg contents in Zuota samples were in the range of 566–676 mg/g. Fortunately, the release of Hg from Zuota samples was very low in simulated gastric juice, and much lower in simulated intestinal juice. Direct contact of Zuota with Caco-2 cells led to dose-dependent cytotoxicity, including activity loss and membrane leakage. The toxicity was closely related to apoptosis, because the caspase 3/7 levels of Caco-2 cells increased after the exposure to Zuota . Interestingly, Zuota samples inhibited the oxidative stress at low concentrations, but the toxicity could be relived by antioxidants. The possible toxicity should be attributed to the cellular uptake of Zuota particulates. Beyond the cytotoxicity, significant differences among Zuota samples from different institutions were observed, suggesting that the preparation process of Zuota had meaningful influence of its biosafety. The implications to the safety and clinical applications of Zuota are discussed.